148k views
2 votes
Solve x

2 - 4x - 7 = 0 by completing the square. What are the solutions?

{2 + , 2 - }
{-2 + , -2 - }
{2 + , 2 + }

1 Answer

5 votes

Explanation:


x^(2) - 4x - 7 = 0

First, let's move the
7 to the right-hand side so we can determine what constant we'll need on the left-hand side to complete the square:


x^(2) - 4x = 7

From here, since the coefficient of the
x term is
-4, we know the square will be
(x - 2) (since
-2 it's half of
-4).

To complete this square, we will need to add
(-2)^(2) to both sides of the equation:


x^(2) - 4x + (-2)^2 = 7 + ^(-2)


x^(2) - 4x + 4 = 7 + 4


(x - 2)^(2) = 11

Now we can take the square root of both sides to figure out the solutions to
x:


x - 2 = \pm √(11)


x = 2 \pm √(11)

User Jaywayco
by
5.4k points